Unpacking the link between principals’ Transformational Leadership and Social Science teachers’ Constructivist Instructional Practices in High School - Sam OL Nguon; Bunhe Hart; Chantheng Meak (Journal of Social Knowledge Education (JSKE), 2026)
Purpose of the study: This study examined the direct relationship between principals’ transformational leadership on  social science teachers’ constructivist instructional practices among high school teachers in Cambodia. It aims to determine how the four dimensions of transformational leadership predict specific social science constructivist instructional practices such as teachers’ autonomy support, teachers’ support and feedback, and cooperative learning which addressing critical literature gap on leadership and social science education.   Methodology:The research employed a quntative design via adapted questionnaires administered to 615 social science teachers across 39 Cambodian high schools in 10 provinces. To ensure robust results, the study utilized a series of statistical techniques which included comfirmatory factor analysis for validity, reliability analysis, birvariate correlations, and multiple regression analysis to examine how transformational leadership dimensions predict various subscales of constructivist instructional practices. Main Findings: The analysis revealed that all four transformational leadership dimensions significantly and positively predicted social science teachers’ constructivist instructional practces, explaining 27% to 38% of the variance. Notably idealized influenceemerged as the strongest predictor, (highlighting the principals’role as an ethical role model). Ultimately, transformational leadership fostered a collaborative environment that encouraged social science teachers to embrace student centered strategies in term of teachers’ autonomy support, teachers’ support and feedback, and cooperative learning techniques in their classrooms. Novelty/Originality of this study: This study provides rare empirical evidence directly linking transformational leadership to social science teachers’ constructivist instructional practices within the specific context of secondary education in Cambodia. By identifying idealized influence as a  primary driver for student-centered teaching. It offers unique cultural insights and practical implications for school leadership development aimed at modernizing spcial study instruction and strengthening critical thinking and civic teaching readiness.